Conception of a YBCO Superconducting ZFC-Magnetic Bearing Virtual Prototype - Arsénio, António (2017)
This paper presents the conception of an original superconducting Frictionless Zero Field Cooling bearing virtual prototype. In previous work also shown in this conference, a viability study of a Zero Field Cooling-superconducting bearing concept was conducted. It showed that the virtual prototype is feasible. Moreover, the simulation studies showed that a Zero Field Cooling superconducting track provides not only effective lateral stability but also higher levitation forces than the commonly used Field Cooling tracks. In this paper the new Zero Field Cooling -bearing virtual prototype is modeled in 3D. The virtual prototype was designed having in mind: i) a future implementation in high density polyurethane, for low temperature robustness; ii) future manufacturing in a three axes CNC milling machine and; iii) future implementation of some parts using an additive manufacturing technique.